Azophenyl appended Schiff base probe for colorimetric detection of Cu2+ in semi‐aqueous medium and live cell imaging. (17th August 2022) - Dev, Samrat; Pandey, Souvik; Maity, Suvendu; Mitra, Debarpan; Das, Gaurav; Murmu, Nabendu; Sinha, Chittaranjan
Abstract: A phenylazo appended ortho ‐vanillin Schiff base scaffold (HAZ) has been used for selective colorimetric sensing of Cu 2+ in semi‐aqueous medium (methanol–water, 1:1, v / v ) in the presence of 16 cations and 20 anions, and the limit of detection is 1.8 × 10 −7  M. The structures of HAZ and Cu (II) complex, [Cu(AZ)2 ], have been characterised by spectroscopic data (UV–Vis, Fourier transform infrared and electron paramagnetic resonance) and established by the single crystal X‐ray diffraction measurement. The Job's plot from the absorption studies has also confirmed the 1:2 stoichiometry of Cu 2+ :HAZ. The absorption spectrum of [Cu (AZ)2 ] has returned to the spectrum of HAZ on the addition of Na2 EDTA solution which is again recovered upon the addition of Cu 2+ solution. Discrete Fourier transform computations were carried out using the coordinates of the X‐ray structures of the compounds, and the molecular functions were used to correlate the solution spectroscopic properties. In addition to this, the probe is treated on MDA‐MB 231 breast cancer cells to check the cytotoxicity. The probe is used for the detection of trace quantity of Cu 2+ in the cancer cell. Abstract : A phenylazo appended ortho‐vanillin Schiff base scaffold (HAZ) acts as selective colorimetric Cu 2+ sensor in presence of 16 cations and 21 anions of the limit of detection 1.8 × 10 –7 M. The Cu(II) complex, [Cu(AZ)2 ], is established by single crystal X‐ray structure determination and EPR measurements. The probe is toxic to MDA‐MB 231 breast cancer cells and detects trace quantity of Cu 2+ in the cancer cell.